The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/jvi.03676-14
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies against Extracellular Domains of Claudin-1 Block Hepatitis C Virus Infection in a Mouse Model

Abstract: Hepatitis C virus (HCV) entry into host cells is a complex process requiring multiple host factors, including claudin-1 (CLDN1).Safe and effective therapeutic entry inhibitors need to be developed. We isolated a human hepatic Huh7.5.1-derived cell mutant that is nonpermissive to HCV, and comparative microarray analysis showed that the mutant was CLDN1 defective. Four hybridomas were obtained, which produced monoclonal antibodies (MAbs) that interacted with the parental Huh7.5.1 cell but not with the CLDN1-defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 44 publications
3
86
0
Order By: Relevance
“…9) We have isolated various hepatic cell mutants resistant to HCV infection, among which CD81-defective 751r cells and CLDN1-defective S7-A cells have been established as clones that are non-permissive to HCV infection. 10,11) Using genetic approaches with these mutant cells, we have confirmed that CD81 and CLDN1 are essential for HCV entry into hepatic cells, which is consistent with other studies. 6,7,12) There is as yet no conclusive evidence for the necessity of OCLN for HCV infection of hepatic cells, although OCLN has been shown by RNA interference (RNAi) experiments to be importantly involved in the infection.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…9) We have isolated various hepatic cell mutants resistant to HCV infection, among which CD81-defective 751r cells and CLDN1-defective S7-A cells have been established as clones that are non-permissive to HCV infection. 10,11) Using genetic approaches with these mutant cells, we have confirmed that CD81 and CLDN1 are essential for HCV entry into hepatic cells, which is consistent with other studies. 6,7,12) There is as yet no conclusive evidence for the necessity of OCLN for HCV infection of hepatic cells, although OCLN has been shown by RNA interference (RNAi) experiments to be importantly involved in the infection.…”
supporting
confidence: 78%
“…[21][22][23] Detection of HCV infection was performed using quantitative reverse transcription-PCR (qRT-PCR) and immunohistochemistry as previously described. 10,11) HCV Pseudoparticle Infection HCV pseudoparticles (HCVpp) were generated as previously described. 24) Briefly, a Gag-Pol packaging construct (Gag-Pol 5349), a transfer vector construct (Luc 126), and an envelope glycoprotein (E1 and E2)-expressing vector [H77, genotype 1a (GenBank accession number JX472009.1); TH, genotype 1b (GenBank accession number AB985268.1); J6, genotype 2a (GenBank accession number AB047639); JFH1, genotype 2a (GenBank accession number AB047639.1); or VSV-G (GenBank accession number M27165)] were transfected into HEK 293T cells.…”
Section: Construction Of Retroviral Expression Vectorsmentioning
confidence: 99%
“…The ability of anti-CLDN-1 human mAbs to inhibit infection by different HCV isolates was not unexpected and was in line with previous observations made with rat and mouse anti-CLDN-1 antibodies (Fofana et al, 2010;Fukasawa et al, 2015;Mailly et al, 2015;Yamashita et al, 2015). Most importantly, mAbs B9X and D10X displayed binding affinity for cell-displayed CLDN-1 and IC 50 values comparable with the rat anti-CLDN-1 mAb OM-7D3, which was recently shown to prevent HCV infection and to clear persistent infection in a human liver-chimeric mouse model without detectable toxicity .…”
Section: Discussionsupporting
confidence: 75%
“…Further experiments in human liver-chimeric mouse models confirmed its potency in preventing HCV infection and eliminating persistent infection in vivo [86]. Pretreatment of another anti-CLDN1 mAb 3A2 targeting CLDN1 extracellular loop also showed protective effect in a chimeric mouse model [87]. Safety profiles of these antibodies were also assessed regarding the levels of human albumin, aspartate transaminase, alanine transaminase and total bilirubin, and potential side effects on the other organs and tight junction integrity.…”
Section: Anti-cldn1 Monoclonal Antibodiesmentioning
confidence: 99%
“…Safety profiles of these antibodies were also assessed regarding the levels of human albumin, aspartate transaminase, alanine transaminase and total bilirubin, and potential side effects on the other organs and tight junction integrity. Further studies were suggested to assess potential immune-mediated adverse effects to ensure its relevance for clinical use [86,87].…”
Section: Anti-cldn1 Monoclonal Antibodiesmentioning
confidence: 99%